Parotid metastasis of an amelanotic melanoma of the scalp: The great masquerader. Issue 4 (8th September 2015) - Neto, Tiago; Nunes, Richard; Amado, Isabel; Balhau, Rui; Marques, Hugo; Sanz, David; Mesquita, Margarida; Pinto, Isabel; Correia‐Sá, Inês; Ferreira, Artur
Abstract: Background: Cutaneous melanoma is often characterized by its pigmented appearance; however, up to 8.1% of such lesions contain little or no pigmentation. Amelanotic melanomas, lesions devoid of visible pigment, present a diagnostic quandary because they can masquerade as many other skin pathologies. Recognizing amelanotic melanoma is even more clinically challenging when it is first detected as a metastasis to the secondary tissue. Methods: We report a rare case of metastasis of an amelanotic melanoma to the parotid gland. Results: A 75‐year‐old man presented with an 8‐month history of a painless, mobile, hardened mass in the right parotid region. Histopathological analysis of a fine‐needle aspiration biopsy of the parotid mass indicated that the mass was melanoma. Careful clinical and radiological examination revealed an 8 mm erythematous papule in the right temporal scalp, initially diagnosed by visual examination as basal cell carcinoma. After right superficial parotidectomy, neck dissection, and excision of the temporal scalp lesion, histological examination revealed the scalp lesion to be amelanotic melanoma. Conclusion: Although metastatic amelanotic melanoma to the parotid gland is a rare diagnosis, the clinician should be familiar with this presentation to increase the likelihood of making the correct diagnosis and delivering prompt treatment. © 2015 Wiley Periodicals, Inc. Head Neck 38: E91–E94, 2016